THE APPLICATION OF WORD OF MOUTH (WOM), SERVICE QUALITY, AND BRAND IMAGE ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE AT AS SYIFAA PHARMACY IN MAJALENGKA - Robi Latansa; Putu Nina Madiawati; Mahir Pradana (PT. Jurnal Center Indonesia Publisher, 2026)
This study investigates how Word of Mouth, service quality, and brand image influence B2B customer loyalty at As-Syifaa Pharmacy in Majalengka, with customer satisfaction acting as a mediating variable. A quantitative approach was applied using the SEM-PLS method, drawing on data from 300 purposively selected customers. The analysis included measurement of validity and reliability, followed by structural model testing to identify both direct and indirect relationships among variables. The findings reveal that Word of Mouth, service quality, and brand image each play a meaningful role in enhancing customer satisfaction, which in turn becomes the strongest predictor of customer loyalty. Satisfaction was also found to mediate the effects of the three antecedent variables, either fully or partially, highlighting its central role in shaping long-term business relationships. These results indicate that building B2B customer loyalty requires more than consistent operational performance; it also depends on maintaining a credible brand reputation and fostering positive relational communication within the business network. Based on these insights, the study recommends strengthening service standards, reinforcing brand consistency, and managing interpersonal communication to support sustainable loyalty among B2B partners.